Observed Kinematics of the Milky Way Nuclear Stellar Disk Region - Rojas-Arriagada, A (EDP Sciences, 2024)
Context. The nuclear region of the Milky Way, within approximately -1° < +1° and -03° < b < +03° (i.e. |l| < 150 pc, |b| < 45 pc), is believed to host a nuclear stellar disk, co-spatial with the gaseous central molecular zone. Previous kinematical studies detected faster rotation for the stars belonging to the nuclear stellar disk, compared to the surrounding regions. Aims. We analyze the rotation velocity of stars at the nuclear stellar disk, and compare them with its analog in a few control fields just outside this region. We limit our analysis to stars in the red clump of the color magnitude diagram, in order to be able to relate their mean de-reddened luminosity with distance along the line of sight. Methods. We used a proper motion catalog, obtained from point spread function photometry on VISTA variables in the Vía Láctea images, to construct maps of the transverse velocity for these stars. We complemented our analysis with radial velocities from the 17th data release of the APOGEE survey. Results. We find that the main difference between the nuclear stellar disk region and its surroundings is that at the former we see only stars moving eastward, which we believe are located in front of the Galactic center. On the contrary, in every other direction, we see the brightest red clump stars moving eastward, and the faintest ones moving westward, as expected for a rotating disk. We interpret these observations as being produced by the central molecular zone, hiding stars behind itself. What we observe is compatible with being produced by just the absence of the component at the back, without requiring the presence of a cold, fast rotating disk. This component is also not clearly detected in the newest release of the APOGEE catalog. In other words, we find no clear signature of the nuclear stellar disk as a distinct kinematical component. Conclusions. This work highlights the need for nearby control fields when attempting to characterize the properties of the nuclear stellar disk, as the different systematics affecting this region, compared to nearby ones, might introduce spurious results. Deep, wide field and high resolution photometry of the inner 4 deg of the Milky Way is needed in order to understand the structure and kinematics of this very unique region of our Galaxy. © The Authors 2024.